FATTY ACID COMPOSITION OF L- DORSI MUSCIE OF INTACT AND CASTRATED KIDS INDUCED BY ZERANOL IMPLANTATION - & et al., Alkass (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
To investigate the influence of zeranol administration by implantation and castration on fatty acids composition, 20 weaned kids (3-4 month old) with an average live weight of 17.3±0.23 kg were divided randomly into two equal main groups, the first was left intact as a control and the 2nd group was castrated. Each main group was then blocked randomly into two sub groups, the 1st was left as control and the 2nd implanted with Ralgro (12mg zeranol). Kids were fed a concentrate adlib and slaughtered after 70 days of fattening. After chilling for 24 hours, a homogenous samples of meat from L.dorsi  muscle was blended for analysis of fatty acid composition. Results revealed that mono unsaturated fatty acid have the highest contribution towards fatty acid of goat meat, followed by saturated fatty acids and poly unsaturated fatty acids. Among individual fatty acids C18:1 contributed highest  followed by  C16:0, C18:0 and C18:3 Neither implanting kids with zeranol nor castration alter significantly the fatty acid profile or PUSF to SFA ratio or the proportion of C18+C18:1/C16.